Lateral pelvic tilt due to musculoskeletal overload in professional ice hockey players - Shtin Banárová, P.; Petríková Rosinová, I.; Popracová, Z.; Ladecký, R. (Zdravotnícke listy, 2019)
Background: Ice hockey is a sport characterized by an asymmetric load on the musculoskeletal system. Therefore, ice hockey players can be expected to experience muscle imbalance in the pelvis. Objective: The aim of this contribution is to determine the incidence of the lateral pelvic tilt in professional ice hockey players. The symmetry of lengths of lower limbs and the occurrence of back pain in the lumbar to lumbosacral parts were also monitored. Sample: The group consisted of professional hockey players (n = 20) who have been playing ice hockey for 10 years or more. They were men aged from 21 to 47 years (average age: 28.95). The control group consisted of randomly selected probands from the non-sporting adult male population (n = 21, age 20 - 40 years, average: 31.33). Methods: A pelvic examination was performed. It included a measurement of the functional length of the lower limbs and an assessment of the pelvic tilt position in the frontal plane. Fisher's exact test was used to verify hypotheses. Results: The pelvis of ice hockey players is significantly more often skewed compared to the general (non-sporting) population (F = 4.94, p = 0.043, Phi = 0.35, N = 41). Significantly more frequent asymmetry of lower limbs lengths was not confirmed (F = 1.75, p = 0.697, Phi = 0.11, N = 41). Pain in the lower back was confirmed in 55% of professional ice hockey players. Conclusion: Research confirmed more skewing of the pelvis of ice hockey players compared to the non-sporting population.